Transformational leadership practices among academic administrators at a public university in Malaysia - Samsudin Norsamsinar, Abd. Razak Ahmad Zainal Abidin, Abdul Jalil Norasibah, Ab. Wahid Hariyaty, Yaakub Kamarul Bahari, (Universiti Pendidikan Sultan Idris, 2017)
Transformational leadership practices among academic administrators at a public university in Malaysia by Samsudin Norsamsinar, Abd. Razak Ahmad Zainal Abidin, Abdul Jalil Norasibah, Ab. Wahid Hariyaty, Yaakub Kamarul Bahari,